The Encyclopedia of Military Biography - Dupuy, Trevor N ; Johnson, Curt and Bongard, David L. (London I.B. Tauris, 1992)
From Agrippa to Zhukov via Cromwell, Hitler, Napoleon, and Schwarzkopf, the 3,000 entries in this reference work provide detailed profiles of the world's greatest military leaders and thinkers. Each entry includes an overview of the subject and details of their major battles and campaigns
Keywords: Military biography